2022
DOI: 10.1371/journal.pone.0261757
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of sexual and reproductive health services delivered to adolescents at Ujala clinics: A qualitative study in Rajasthan, India

Abstract: The Adolescent Friendly Health Clinic (AFHCs), a key component of the Government of India’s National Adolescent Health Programme a.k.a. Rashtriya Kishor Swasthya Karyakram (RKSK), aims to increase the accessibility and utilization of sexual-reproductive health services by adolescents and youth. However, low quality of care provided at AFHCs by counsellors calls for attention. We, thus, explore both the clients’ and providers’ perspectives using the World Health Organization’s (WHO) global standards for quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Similar findings have been observed in the state of Ahmedabad24 and West Bengal 27. Moreover, AFHCs in both the study states were accessible by local transport, unlike AFHCs in Rajasthan, where ease of accessibility was a major concern 28. Study results showed that the privacy and confidentiality of the patient were maintained, as all case records were kept in secured place and only authorised personnel (counsellor, ANM and MO) had access to retrieve them.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar findings have been observed in the state of Ahmedabad24 and West Bengal 27. Moreover, AFHCs in both the study states were accessible by local transport, unlike AFHCs in Rajasthan, where ease of accessibility was a major concern 28. Study results showed that the privacy and confidentiality of the patient were maintained, as all case records were kept in secured place and only authorised personnel (counsellor, ANM and MO) had access to retrieve them.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the absence of IEC materials, specifically in the regional language at the health facility, can act as a hurdle in utilisation of the health services by adolescents. Studies across various Indian states including Gujarat (Ahmedabad),24 Rajasthan28 replicate the finding of limited IEC material at the AFHCs, while AFHCs in West Bengal27 provided IEC material on SRH. To make the Indian AFHC compliant to this benchmark, key is to have a combination of no-tech and high-tech resources in AFHCs that may assist in catering to a wider range of literacy levels of adolescents.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Adolescent reproductive health information service is a form of two-way communication between teachers and students in solving problems faced by adolescent reproductive health activities. Adolescent reproductive health information services aim to assist adolescents by exploring the conditions and problems they face, so that adolescents are able to make the right decisions in solving problems and what they see around them (Dayal & Gundi, 2022) Adolescent reproductive health information service is a form of two-way communication between teachers and students in solving problems faced by adolescent reproductive health activities (binti Shuib, bin Mohd Yasin, & bin Tahar, 2022). Adolescent reproductive health information services aim to help adolescents by exploring the conditions and problems they face, so that adolescents are able to make the right decisions in solving problems and what they see around them.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, studies in Rajasthan reflect that the Ujala counsellors had limited knowledge and competencies in providing accurate information on the SRH topics. 10 In addition, the gaps in the availability and utilisation of IEC materials, referral linkages and the maintenance of privacy and confidentiality of the clients exacerbate the issue. 11 Overall, the RKSK programme in Rajasthan had crucial implementation issues, and the current Ayushman Bharat School Health Programme hardly covers SRH topics.…”
mentioning
confidence: 99%